Balancing irrigation and hydropower: case study from southern Sri Lanka - Molle, Francois; Jayakody, Priyantha; Ariyaratne, Badugodahewa Ranjith; Somatilake, H.S. (International Water Management Institute, 2005)
This report analyzes a case from southern Sri Lanka, where the Samanalawewa dam and the Kaltota Irrigation Scheme (KIS) compete for the water of the Walawe river. At the catchment level, it is shown that dam releases are well attuned to the needs of KIS and to the occurrences of natural runoff, and that little of the dam water is "lost" to the river.